Migration and transformation of heavy metals in glass-ceramics and the mechanism of stabilization - Yilin, Pi; Wenhua, Zhang; Yunsheng, Zhang; Wanting, Zou; Zaixiang, Zhang; Fan, Wu (Ceramics international, 2021)
There are many kinds of heavy metals in tailings and other solid waste, and the content is high. Glass-ceramic as a promising final product not only has excellent physical properties, but also can effectively solidify heavy metals. However, the study on the stabilization of single heavy metal in glass-ceramics is still limited. Therefore, zinc and copper, two common heavy metals in tailings, were used as representatives to conduct this research to find the phase transformation and the stabilization mechanism. X-ray diffraction (XRD), Scanning electron microscopy (SEM-EDS), X-ray photoelectron spectroscopy (XPS), and Inductively coupled plasma source mass spectrometer (ICP-MS) were used as the characterization methods. The results showed that the main crystallization phase was diopside (CaMgSi2O6). With the increase of zinc and copper content, the integrity of glass network structure got worse, and the viscosity of glass was decreased. So, the volume density and shrinkage of glass-ceramics were also increased. The shrinkage for glass-ceramics with different content of zinc was from 16.1% to 20.2%, and the volume density was increased from 2.3 g/cm3 to 2.54 g/cm3. The glass-ceramics with different content of copper shows similar trend. The shrinkage ranged from 16.1% to 20.4%, and the volume density was increased from 2.32 g/cm3 to 2.56 g/cm3. For samples with different zinc content, the bending strength was increased from 135 MPa to 161 MPa. On the contrary, for samples with different content of copper first increased to 148 MPa and then decreased to 133 MPa. The curing process of zinc and copper in glass-ceramic shows different trends. When the content of heavy metal is less than 1.5 wt%, zinc and copper all remain in the diopside phase in the form of solid solution. With increased of the heavy metal content, zinc is stably cured in the glass-ceramic as the petedunnite phase (CaZnSi2O6), while copper is remained in the glass-ceramic in the phase of CuAlO2. Heavy metals are well solidified in glass ceramics, so the leaching concentration is much lower than the standard limit, and the leaching rate tends to be stable when the heavy metal content up to 1.5 wt%. The results showed that the conversion of Zn-rich and Cu-rich tailings and other solid waste into environmentally friendly glass-ceramics had great potential and reliability.